PENINGKATAN KOMPETENSI GURU MENGGUNAKAN WHATSAPP GROUP PADA PEMBELAJARAN MASA PANDEMI MELALUI WORKSHOP BERBANTUKAN ZOOM MEETING DI SMA NEGERI 1 GAROGA SEMESTER 1 TAHUN PELAJARAN 2021/2022 - Sormin, Bosar (Hijri, 2022)
The research aims to increase teacher competence in using whatsapp groups during the pandemic learning through workshops assisted by zoom meetings. This research is School Action Research (PTS). The research subjects were 9 teachers. Data collection techniques with observation and documentation techniques. Data validation with triangulation techniques. Methods of data analysis using qualitative data analysis. Based on the research results, the implementation of workshops assisted by zoom meetings has been proven to be able to increase teacher competency in using WhatsApp groups in learning during a pandemic. This is evidenced by the increase in the results of assessing the competence of teachers in using whatsapp groups in learning during the pandemic in the initial conditions the average value was 47.64 and was in the Less (K) category, increasing in the first cycle with an average score of 70.42 and included in the Enough category (C) and in the second cycle with an average value of 91.11 and included in the Very Good category (SB). As for the increase in individual teacher competence, it can be explained that in the initial conditions of the 9 teachers, not a single teacher was declared complete, in the first cycle it increased to 5 teachers (55.56%) and in the second cycle all teachers (100%) were declared complete. From the explanation above, it can be concluded that the holding of workshops assisted by zoom meetings has been proven to be able to increase the competence of teachers at SMA Negeri 1 Garoga in using WhatsApp groups during pandemic learning Keywords:Competency, Whatsapp Group, Workshop, Zoom MeetingThe research aims to increase teacher competence in using whatsapp groups during the pandemic learning through workshops assisted by zoom meetings. This research is School Action Research (PTS). The research subjects were 9 teachers. Data collection techniques with observation and documentation techniques. Data validation with triangulation techniques. Methods of data analysis using qualitative data analysis. Based on the research results, the implementation of workshops assisted by zoom meetings has been proven to be able to increase teacher competency in using WhatsApp groups in learning during a pandemic. This is evidenced by the increase in the results of assessing the competence of teachers in using whatsapp groups in learning during the pandemic in the initial conditions the average value was 47.64 and was in the Less (K) category, increasing in the first cycle with an average score of 70.42 and included in the Enough category (C) and in the second cycle with an average value of 91.11 and included in the Very Good category (SB). As for the increase in individual teacher competence, it can be explained that in the initial conditions of the 9 teachers, not a single teacher was declared complete, in the first cycle it increased to 5 teachers (55.56%) and in the second cycle all teachers (100%) were declared complete. From the explanation above, it can be concluded that the holding of workshops assisted by zoom meetings has been proven to be able to increase the competence of teachers at SMA Negeri 1 Garoga in using WhatsApp groups during pandemic learning.